The Influence of the Load-bearing Ability on an Affected Lower Extremity on the Standing Balance of Stroke Hemiplegic Subjects - ASAYAMA, Shinji (Rigaku ryoho kagaku, 1999)
The relation between the load-bearing ability of an affected lower extremity and standing balance, and the influence of load exercise on the standing balance were examined for 14 stroke hemiplegic subjects. The apparatus for balance analysis was used to measure, during static standing, the length and area of instability of the center of gravity, and the body weight load on the affected lower extremity. The subject with a higher load on the affected lower extremity showed a short length and small area of instability of the center of gravity, and was thus considered to have stable standing balance. The four subjects who had underwent load exercise for the affected lower extremity, exhibited an increase in the load on the affected lower extremity and a decrease in the length and area of the center of gravity, which suggested that their standing balance became more stable. These results suggested that not only the balance exercise during standing or gait, but also the exercise for improving load-bearing ability of the affected lower extremity is necessary for hemiplegic patients after stroke.